AQP9 and ZAP70 as immune-related prognostic biomarkers suppress proliferation, migration and invasion of laryngeal cancer cells - Li Ren; Ping Li; Zhouping Li; Quan Chen (BMC Cancer, 2022)
Abstract Background Laryngeal cancer represents a common malignancy that originates from the larynx, with unfavorable prognosis. Herein, this study systematically analyzed the immune signatures of laryngeal cancer and to evaluate their roles on tumor progression. Methods Differentially expressed immune-related genes (IRGs) were screened between laryngeal cancer and normal tissues from TCGA dataset. Then, two prognosis-related IRGs AQP9 and ZAP70 were analyzed by a series of survival analysis. Based on them, molecular subtypes were constructed by unsupervised cluster analysis. Differences in survival outcomes, HLA expression and immune cell infiltrations were assessed between subtypes. Expression of AQP9 and ZAP70 was validated in laryngeal cancer tissues and cells by RT-qPCR and immunohistochemistry. After silencing and overexpressing AQP9 and ZAP70, CCK-8, EdU, wound healing and transwell assays were performed in TU212 and LCC cells. Results Totally, 315 IRGs were abnormally expressed in laryngeal cancer. Among them, AQP9 and ZAP70 were distinctly correlated to patients’ prognosis. Two subtypes were developed with distinct survival outcomes, HLA expression and immune microenvironment. Low expression of AQP9 and ZAP70 was confirmed in laryngeal cancer. AQP9 and ZAP70 up-regulation distinctly suppressed proliferation, migration, and invasion of laryngeal cancer cells. The opposite results were investigated when their knockdown. Conclusions Our findings revealed the roles of AQP9 and ZAP70 in progression of laryngeal cancer, and suggested that AQP9 and ZAP70 could potentially act as candidate immunotherapeutic targets for laryngeal cancer.